El sistema de justicia constitucional y la especialidad en materia constitucional del juez ecuatoriano. - Almeida, Roberto A. (2021)
The present research work aims as overall objective to analyze the incidence of the specialty in constitutional matters of the Ecuadorian Judge in the constitutional justice model. The research methodology was designed with a qualitative approach; it is of descriptive and critical legal type with a documentary, bibliographic, field design; applying the systematic legal method to analyze the real and current legal information related to the research topic for which data collection techniques and instruments were used such as (I) an observation and documentary analysis sheet that was applied to the processes of jurisdictional actions that appear in the System of the Judicial Council in Otavalo, (II) a survey that was applied to 9 judges of the first instance, and (III) a population sample of 147 lawyers in the free professional practice of the law to know their criteria related to the investigation. The most relevant results of the study allow us to conclude that significant percentages of inadmissible, abandoned, appealed, and revoked cases were detected. None of the processes was selected for constitutionality review and control by the Constitutional Court. Most of the first-level judges acknowledge that they have no specialty in constitutional matters. The process of selection of the judges of the first instance; does not consider the specialty in constitutional matters as a requirement, nor does the initial training course offered by the School of the Judicial Function of the Council of the Judiciary for the winners of the contest, it includes specific contents of the constitutional justice model, so at least in this formal aspect, the selection of judges does not guarantee their specialty in constitutional matters.